2012
DOI: 10.1126/scisignal.2002908
|View full text |Cite
|
Sign up to set email alerts
|

An Interaction Between BZR1 and DELLAs Mediates Direct Signaling Crosstalk Between Brassinosteroids and Gibberellins in Arabidopsis

Abstract: Plant growth and development are coordinated by several groups of small-molecule hormones, including brassinosteroids (BRs) and gibberellins (GAs). Physiological and molecular studies have suggested the existence of crosstalk between BR and GA signaling. We report that BZR1, a key transcription factor activated by BR signaling, interacts in vitro and in vivo with REPRESSOR OF ga1-3 (RGA), a member of the DELLA family of transcriptional regulators that inhibits the GA signaling pathway in Arabidopsis thaliana. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
238
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(243 citation statements)
references
References 66 publications
4
238
0
1
Order By: Relevance
“…For example, it has been demonstrated that ABA inhibits plant growth by suppressing BR signaling downstream of BR receptor (Zhang et al 2009). An antagonistic interaction has been also evidenced between BRs and gibberellins, since the GA repressor DELLA directly interacts with BZR1 to inhibit its DNA binding and thus transcription activity in controlling photomorphogenesis (Sun et al 2010;Li et al 2012). In this scenario, given the apparent involvement of multiple phytohormones also in nitrogen signalling (Kiba et al 2011), one future challenge will be to understand how BRs interact with other phytohormones to respond to N deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been demonstrated that ABA inhibits plant growth by suppressing BR signaling downstream of BR receptor (Zhang et al 2009). An antagonistic interaction has been also evidenced between BRs and gibberellins, since the GA repressor DELLA directly interacts with BZR1 to inhibit its DNA binding and thus transcription activity in controlling photomorphogenesis (Sun et al 2010;Li et al 2012). In this scenario, given the apparent involvement of multiple phytohormones also in nitrogen signalling (Kiba et al 2011), one future challenge will be to understand how BRs interact with other phytohormones to respond to N deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining genes (ZmBZR1, ZmBZR4, ZmBZR5, ZmBZR9, ZmBZR10 and ZmBZR11) were ubiquitously expressed in all the tissues examined, suggesting that they could function as growth regulators during maize development. In fact, recent studies have demonstrated that BR signaling pathway is required to regulate hypocotyl cell expansion (Gallego-Bartolomé et al 2012;Li et al 2012;Oh et al 2012), as well as, to promote the transition from meristematic cells to primordial cells in the shoot (Oh et al 2011;Zhiponova et al 2013). In the root apex, BRs are further involved in controlling root growth, both coordinating root meristem size and also root cell elongation Heyman et al 2013;Vilarrasa-Blasi et al 2014;Vragovic et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The GA signaling negative regulator, DELLA protein, interacts with BZR1/BES1 and inhibits their function. Thus, GA can release the inhibition of DELLA on BZR1/BES1 to induce downstream BR responses in Arabidopsis (Bai et al, 2012;Gallego-Bartolomé et al, 2012;Li et al, 2012). Although great progress has been made in this aspect, the knowledge we have now is far from enough to understand the interaction network of BR and GA. More related research work needs to be carried out.…”
mentioning
confidence: 99%
“…For instance, this is the case for several PIFs (de Lucas et al, 2008;Feng et al, 2008;Cheminant et al, 2011;Gallego-Bartolomé et al, 2011) and BZR1 (Bai et al, 2012;Gallego-Bartolomé et al, 2012;Li et al, 2012). In other cases, the interaction with the TF occurs in the vicinity of the promoters of certain genes to promote their expression (Lim et al, 2013;Park et al, 2013).…”
Section: Gai Counteracts Rap23-mediated Transcriptional Activationmentioning
confidence: 99%